2017
DOI: 10.1016/j.annals.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Diaspora tourism and well-being: A eudaimonic view

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 10 publications
0
35
0
Order By: Relevance
“…2016 16 (Boukas & Ziakas, 2016); (Filep, 2016); (Gholipour, Tajaddini, & Nguyen, 2016); (Hartwell, Willis, Page, Ladkin, Fyall, & Hemingway, 2016); (Hjalager, Tervo-Kankare, & Tuohino, 2016); (Kim, Chua, Boo, Lee, & Han, 2016); (Krishnamoorthy & Ramachandran, 2016); (Mäkelä & Kinnunen, 2016); (Naidoo & Sharpley, 2016); (Nawijn, 2016); (Pratt, McCabe, & Movono, 2016); (Pyke et al, 2016); (Rivera, Croes, & Lee, 2016); (Uysal, Sirgy, Woo, & Kim, 2016); (Vogt, Jordan, Grewe, & Kruger, 2016); (Volo, 2016 (Laing & Frost, 2017); (Li & Chan, 2017); (Park, Lee, & Lee, 2017); (Tokarchuk, Maurer, & Gabriele, 2017); (Wu, Ai & Cheng, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2016 16 (Boukas & Ziakas, 2016); (Filep, 2016); (Gholipour, Tajaddini, & Nguyen, 2016); (Hartwell, Willis, Page, Ladkin, Fyall, & Hemingway, 2016); (Hjalager, Tervo-Kankare, & Tuohino, 2016); (Kim, Chua, Boo, Lee, & Han, 2016); (Krishnamoorthy & Ramachandran, 2016); (Mäkelä & Kinnunen, 2016); (Naidoo & Sharpley, 2016); (Nawijn, 2016); (Pratt, McCabe, & Movono, 2016); (Pyke et al, 2016); (Rivera, Croes, & Lee, 2016); (Uysal, Sirgy, Woo, & Kim, 2016); (Vogt, Jordan, Grewe, & Kruger, 2016); (Volo, 2016 (Laing & Frost, 2017); (Li & Chan, 2017); (Park, Lee, & Lee, 2017); (Tokarchuk, Maurer, & Gabriele, 2017); (Wu, Ai & Cheng, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…de Bloom et al (2017) concluded that, when traveling, individuals showed higher levels of hedonic wellbeing and ruminative thinking was lower when compared to leisure time at home. Li and Chan (2017) found six dimensions by which diaspora tourism promotes tourists' subjective wellbeing. Laing and Frost (2017) phenomenological study of travel experiences in Italy found also six wellbeing dimensions and hedonic and eudaimonic wellbeing notions were found in the narratives.…”
Section: Reference Location Paper Aim(s)mentioning
confidence: 99%
“…Place attachment is considered as a fundamental human need and a natural condition of human existence with deep implications to one's subjective well-being (Li & Chan, 2017;Manzo & Devine-Wright, 2014;Morgan, 2010;Scannell & Gifford, 2017). The importance of places in the contemporary world may have grown, despite the increased mobility and globalisation (Gustafson, 2006).…”
Section: Place and Place Attachmentmentioning
confidence: 99%
“…The place of ancestral home played a significant role in reinforcing migrants' self‐continuity and rootedness. It is associated with one's origin, roots, ancestry, and identity and was considered as the prerequisite to integrate various life experiences into a coherent life story (Sani, ; Lewicka, ; Li & Chan, ). As such, migrants tend to seek a stable sense of place and identity through constructing different types of connections with their ancestral home, in order to assure a coherent life story and a stable sense of self (Liu, ; Twigger‐Ross & Uzzell, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many recent studies have noted that return travel provides migrants with a transformative experience by connecting them physically, culturally and socially to their ancestral home (Alexander, Bryce, & Murdy, 2017;Weaver et al, 2017;Huang, King, & Suntikul, 2017). Although some of these studies have engaged with the social functions of diasporic return in one way or another (Marschall, 2017;Pelliccia, 2018;Li & Chan, 2017), the links between diaspora tourism and social capital have been insufficiently discussed despite the growing popularity of home return trips (Gafter & Tchetchik, 2017;Etemaddar, Duncan, & Tucker, 2016).…”
Section: Introductionmentioning
confidence: 99%